Variation factors of paraoxonase in blood and in HDL lipoproteins in dairy cow - Trevisi, E.; Grossi, P.; Bacchetti, et al., T. (Progress in Nutrition, 2012)
Paraoxonase-1 (PON) is an antioxidant enzyme synthesized by liver and mainly associated with high density lipoproteins (HDL). Aim of this study was to investigate the alterations of PON1 activity in plasma (pPON) or bound to HDL (HDL-PON) in relation to inflammatory conditions and physiological stages. Between -30 to +300 days from calving, 9 cows were monitored for metabolic and inflammatory profiles, milk yield, body condition score and feed intake. Cows were divided in 2 groups based on their response to postpartum inflammatory stimulus (high and low Liver Functionality Index: HI-LFI and LO-LFI). pPON decreased after calving (P<0.05) and was directly correlated with milk yield (r=0.48; P<0.01), albumins and other indirect indexes of negative acute phase proteins (-APP: cholesterol and retinol binding protein). On the contrary, pPON was inversely related with the +APP (haptoglobin, ceruloplasmin) and related indexes (bilirubin, ROM). The correlation between pPON and HDL-PON was low. After calving, the HI-LFI vs LO-LFI group had higher –APP and pPON levels, lower HDL-PON level and displayed better performances. Overall results demonstrated that pPON has a similar behavior in comparison to –APP, confirming previous data. The results suggested that pPON activity could represent an useful marker to assess the severity of postpartum inflammatory phenomena and their consequences. Fattori di variazione della paraoxonasi plasmatica e nelle lipoproteine HDL nella bovina da latte La paraoxonasi-1 (PON1) è un enzima antiossidante di sintesi epatica associato principalmente alle lipoproteine ad alta densità (HDL). Scopo dello studio è stato quello di valutare le variazioni di PON1 nel plasma (pPON) o nelle HDL (HDL-PON) in relazione allo stato infiammatorio ed allo stadio fisiologico. Nove bovine sono state controllate tra -30 e +300 giorni dal parto per: marcatori ematici dello stato infiammatorio, produzione di latte, stato di ingrassamento, ingestione di alimenti. Le bovine sono state divise in 2 gruppi sulla base della loro risposta allo stimolo infiammatorio post partum (alto e basso Liver Functionality Index: HI-LFI e LO-LFI). La pPON ha mostrato un calo temporaneo dopo il parto (P<0,05) e la sua attività è risultata correlata con la produzione di latte (r=0,48; P<0,01), le albumine ematiche ed altri indici indiretti delle proteine negative di fase acuta (-APP: colesterolo, retinolo). Invece correlazioni inverse sono state osservate con le +APP (apto-globina e ceruloplasmina) ed altri indici correlati (es. bilirubina, ROM). La correlazione tra pPON e HDL-PON è risultata modesta. Dopo il parto le bovine HI-LFI (vs LO-LFI), oltre a livelli più alti di -APP e di pPON, hanno mostrato migliori performance. Tali risultati confermano che nella bovina la pPON ha un andamento simile a quello delle –APP. Questa associazione supporta l’utilità della pPON per valutare la gravità della risposta infiammatoria nel postparto e le sue conseguenze.